Analisis Resepsi Pelecehan Seksual di Dunia Pendidikan (Resepsi Mahasiswa PMII Universitas Nasional Tentang Isu Pelecehan Seksual Pada Akun X @Tungtung1906) - Salsabililah, Agriness Marsyha; Yusmawati, Yusmawati (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
The internet and social media have facilitated the dissemination of information regarding social issues within society. Social media platforms like X enable users to share their experiences and views help raise public awareness. Information on social media is received in diverse ways by its users. Many social issues are posted by social media users, including the issue of sexual harassment, as seen in the posts from the @tungtung1906 account, which shares information about sexual harassment incidents experienced in the higher education environment where the user studies. These posts are received by other users. This study aims to understand the reception of PMII National University students regarding the issue of sexual harassment posted by the @tungtung1906 account. The research method uses a qualitative approach, with data collection techniques through in-depth interviews. The results show that PMII students are in both Dominant and Negotiated positions. In the dominant position, some students accept and support the narrative presented by the @tungtung1906 account as a true representation of the existing problem. Moreover, they support the way the @tungtung1906 account conveys the message about sexual harassment and agree on the importance of openly discussing this issue to raise public awareness and encourage positive change. In the negotiated position, some students understand the issue but adjust their views by considering cultural, educational, and personal experience factors.